Wielkopolskie gościńce typowe – przykład standaryzacji i indywidualizacjiw polskim pejzażu architektonicznym doby gierkowskiej - Bryl-Roman, Weronika (Człowiek i Społeczeństwo, 2017)
The purpose of this study is to present a 1970’s project of repeatable inns, designed for Great Poland (a region in the western Poland) as an example of mixed tendencies – of standardisation (modern external shell, uniformed road advertising) and individualisation (arrangement of the interior architecture, naming, cuisine), applied to achieve various aims of the social policy of the communist reality of that time (such as promotion of attractive leisure, folklore, traditional professions and tourism). More than thirty inns, situated by the main roads in areas noted for their outstanding scenery and cultured features, were designed to minimalise a degree of contrast. The adaptation of the architecture to the terrain relief and to the forms of natural environment brought out the most valuable elements of the scenery and expressed the respect for landscape aesthetics. The project seen from a cultural studies’ perspective reveals various aspects and possible readings. Although the inns contribute to the Polish cultural heritage, they remain unprotected and at least some of them may soon disappear. To fully illustrate the project’s importance, the paper offers also some technical and documentary details. Weronika Bryl-Roman, Wielkopolskie gościńce typowe – przykład standaryzacji i indywidualizacji w polskim pejzażu architektonicznym doby gierkowskiej [The „typical inns” of Wielkopolska – an example of standardization and individualization in the Polish architectural landscape of the Gierek era], edited by W. Bryl-Roman, „Człowiek i Społeczeństwo” vol. XLIII: Projektowanie w latach 70. [Designing in the 1970s], Poznań 2017, pp. 165-190, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271.